The other feminists : activists in the liberal establishment - Hartmann, Susan M. (Yale University Press, 1998)
"This book enriches our understanding of the women's movement in the United States by showing how feminists captured a place for their goals on the agendas of four male-dominated liberal organizations in the 1960s and 1970s: the International Union of Electrical Workers, the American Civil Liberties Union, the National Council of Churches, and the Ford Foundation. Susan M. Hartmann examines the efforts of women and men who had few ties to the independent women's movement - and thus have been neglected in studies of second-wave feminism - but who nonetheless contributed substantially to the spread of feminist ideas and practices into the mainstream of American society. These establishment groups furnished money, legitimacy, and access to the critical arenas of public opinion and government." "Revising the common view that the second wave of feminism was a white middle-class phenomenon, Hartmann discovers significant numbers of women of color and working-class women who pushed feminist agendas."--Jacket